Spatial Distribution of Tsetse Flies and Trypanosome Infection Status in a Vector Genetic Transition Zone in Northern Uganda. (1st June 2022) - Opiro, Robert; Moses, Okello Allele; Opoke, Robert; Oloya, Francis A.; Nakafu, Esther; Iwiru, Teresa; Echodu, Richard; Malinga, Geoffrey M.; Bargul, Joel L.; Opiyo, Elizabeth A.
Abstract : Background . Tsetse flies are vectors of the genus Trypanosoma that cause African trypanosomiasis, a serious parasitic disease of people and animals. Reliable data on the vector distribution and the trypanosome species they carry is pertinent for planning sustainable control strategies. This study was carried out to estimate the spatial distribution, apparent density, and trypanosome infection rates of tsetse flies in two districts that fall within a vector genetic transition zone in northern Uganda. Materials and Methods . Capturing of tsetse flies was done using biconical traps deployed in eight villages in Oyam and Otuke, two districts that fall within the vector genetic transition zone in northern Uganda. Trapped tsetse flies were sexed and morphologically identified to species level and subsequently analyzed for detection of trypanosome DNA. Trypanosome DNA was detected using a nested PCR protocol based on primers amplifying the internal transcribed spacer (ITS) region of ribosomal DNA. Results . A total of 717 flies (406 females; 311 males) were caught, all belonging to the Glossina fuscipes fuscipes species. The overall average flies/trap/day (FTD) was 2.20 ± 0.3527 (mean ± SE ). Out of the 477 (201 male; 276 females) flies analyzed, 7.13% (34/477) were positive for one or more trypanosome species. Three species of bovine trypanosomes were detected, namely, Trypanosoma vivax, 61.76% (21/34), T. congolense, 26.47% (9/34), and T. brucei brucei, 5.88% (2/34), and two cases of mixed infection of T. congolense and T. brucei brucei, 5.88% (2/34). The infection rate was not significantly associated with the sex of the fly (generalized linear model (GLM), χ 2 = 0.051, p = 0.821, df = 1, n = 477 ) and district of origin (χ 2 = 0.611, p = 0.434, df = 1, n = 477 ). However, trypanosome infection was highly significantly associated with the fly's age based on wing fray category (χ 2 = 7.56, p = 0.006, df = 1, n = 477 ), being higher among the very old than the young. Conclusion . The relatively high tsetse density and trypanosome infection rate indicate that the transition zone is a high-risk area for perpetuating animal trypanosomiasis. Therefore, appropriate mitigation measures should be instituted targeting tsetse and other biting flies that may play a role as disease vectors, given the predominance of T. vivax in the tsetse samples.